2011
DOI: 10.1515/bc.2011.174
|View full text |Cite
|
Sign up to set email alerts
|

The influenza virus PB1-F2 protein has interferon antagonistic activity

Abstract: PB1-F2 is a nonstructural protein of influenza viruses encoded by the PB1 gene segment from a +1 open reading frame. It has been shown that PB1-F2 contributes to viral pathogenicity, although the underlying mechanisms are still unclear. Induction of type I interferon (IFN) and the innate immune response are the first line of defense against viral infection. Here we show that influenza A viruses (IAVs) lacking the PB1-F2 protein induce an enhanced expression of IFN-β and IFN-stimulated genes in infected epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 40 publications
0
57
0
Order By: Relevance
“…An early delay in innate immune activation has been observed in lung tissues of mice infected with a sublethal mouse-adapted virus carrying the PB1-F2 N66S mutation (3), supporting a growing body of evidence from in vitro studies that PB1-F2 delays innate immune activation (5,30). Here we observed that only the N66S-carrying 1918 PB1-F2 protein was associated with inhibition of IFN-␣, IL-1␤, and IL-6 induction in ferret nasal wash cells at day 1 after infection, providing further evidence for an immunomodulatory role of full-length PB1-F2 proteins with this mutation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…An early delay in innate immune activation has been observed in lung tissues of mice infected with a sublethal mouse-adapted virus carrying the PB1-F2 N66S mutation (3), supporting a growing body of evidence from in vitro studies that PB1-F2 delays innate immune activation (5,30). Here we observed that only the N66S-carrying 1918 PB1-F2 protein was associated with inhibition of IFN-␣, IL-1␤, and IL-6 induction in ferret nasal wash cells at day 1 after infection, providing further evidence for an immunomodulatory role of full-length PB1-F2 proteins with this mutation.…”
Section: Discussionmentioning
confidence: 90%
“…In mice, introduction of the entire 1918 PB1-F2, or the N66S mutation alone, into the context of the mouse-adapted H1N1 WSN/33 strain resulted in an increased production of proinflammatory cytokines at later infection stages (3,4,19). However, further characterization of the N66S mutant revealed decreased type I IFN production during the initial phase of the infection (3,5,30).…”
Section: Discussionmentioning
confidence: 99%
“…PB1-F2 truncations and IFN-␤ expression. PB1-F2 from mouse-adapted viruses alters type I interferon production in some cell types (22)(23)(24)28). We transfected A549 and DF1 cells with the PB1-F2 plasmids and measured IFN-␤ expression at various time points using the TaqMan assay qRT-PCR.…”
Section: Evolution Of Pb1-f2 Truncations In Avian and Mammalian Virusesmentioning
confidence: 99%
“…Several possible mechanisms have been suggested, including mitochondrial targeting and proapoptotic activity (8,9,19), enhancing PB1 function (20), and inhibition (21)(22)(23)(24)(25)(26)(27) or enhancement (28) of the IFN-␤ response. PB1-F2 has also been linked to bacterial infections following IAV infection (29)(30)(31)(32).…”
mentioning
confidence: 99%
“…NS1, plays a critical role during infection by neutralizing cellular antiviral responses and increasing viral protein synthesis, while decreasing the synthesis of cellular proteins (reviewed by Hale et al [8], Lin et al [9], and Krug et al [10]). The role of neutralizing antiviral defenses has been recently shown to be shared by another viral protein produced by a limited number of viral strains: The so-called PB1-F2 protein, a 90 amino acid protein produced by an alternative ORF contained within the PB1 gene segment [11][12].…”
Section: A Nuclear Rna Virus: the Life Cycle Of Influenza A Virusmentioning
confidence: 99%